REVIEW OF INDONESIAN NATIONAL WORK COMPETENCY STANDARDS FROM THE PROFESSIONAL STANDARDIZATION NATIONAL AGENCY IN CREATIVE MEDIA STANDARD POLYTECHNICS JAKARTA - Zalzulifa Zalzulifa; Nasaruddin Nasaruddin; Purnomo Ananto (Politeknik Negeri Media Kreatif, 2019)
The research objective is to describe and interpret the extent to which the level of requirements for the Indonesian National Work Competency Standards (SKKNI) from the National Professional Standardization Agency (BNSP) applied to the State Polytechnic of Creative Media (PoliMedia)